Survey Influencing Factors on Prenatal Care in mothers referring to health care ‎centers in Rasht city in ‎‏2008‏ - fataneh bakhshi; nasrin mokhtari; shahin jefruodi; jila shekani; moohamad abasi; zahra atrkarruoshan (Guilan University of Medical Sciences, 2009)
Introduction: Prenatal care is an important tool to determine and decrease the risks of delivery ‎outcome such as low birth weight, death or mortality during first year of life. The main objective of ‎these care are healthy delivery without jeopardizing mothers health. Some factors prohibit receiving ‎proper and promote prenatal care and cause mother and child health complications. Knowing these ‎factors to identify groups at risk and needed areas for‏ ‏intervention is essential in every society.‎ Objective: To determine mothers receiving prenatal care from health centers in Rasht and ‎influencing factors from their view in ‎‏2008‏‎.‎ Methods: This descriptive study surveyed ‎‏354‏‎ mothers referring to health centers in Rasht city who ‎were chosen by cluster sampling. Data collection tool was a ‎‏3‏‎ part questionnaire.‎ Results: Findings showed that ‎‏53.4%‏‎ of women receiving insufficient prenatal care. There was a ‎significant correlation of care and employment condition (p=‎‏0.026‏‎) level of spouse s education ‎‎(p=‎‏0.042‏‎) and income (p=‎‏0.005‏‎). The most effective factors on receiving prenatal care from ‎mothers view were "to know the manner and number of prenatal care".(‎‏85.3%‏‎). ‎ Conclusion: In existence of prenatal care in health centers, almost half of women do not use these ‎care provided. Among barriers to utilization of care were not knowing the manner and number of ‎prenatal care, compliance with the women's privacy in time of providing care and providers manner ‎of communication in health centers. Some of women's demographic and family characteristics were ‎also barriers to utilization of prenatal care which provider's attention to these characteristics seems ‎important in promotion of receiving better prenatal care. ‎